Distributed Non-Convex Input-Constrained Consensus Problem for High-Order Discrete-Time Multi-Agent Systems Subject to Switching Topologies, and Time Delays - Hongqiu Zhu (IEEE Access, 2019)
In this paper, a distributed consensus problem is considered for high-order discrete-time multi-agent systems subject to non-convex input constraints and switching topologies. A constrained control algorithm is provided to drive all agents to reach consensus on their position states. It proves that this algorithm is robust to the arbitrarily bounded time delays as long as the communication topologies jointly have spanning trees. Finally, we show the effectiveness of the proposed distributed algorithm by a numerical example.